KRIPIK AYAM BUMBU BALI SEBAGAI ALTERNATIF USAHA BAGI IBU RUMAH TANGGA - Ni Nyoman Ayu Suryandari; Ida Ayu Nyoman Yuliastuti; Siluh Putu Natha Primadewi (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
Chicken Chips is a traditional snack cultivated by people from various circles. It's tasty to make chicken chips can be enjoyed as a snack when casual or side dishes when eating. But along with the many parties who like, chicken chips can now be a business opportunity with a turnover of millions of dollars. This opportunity is utilized by Mrs. Putu Yuliana (43) by establishing a business of making chicken chips